IN VITRO IMMUNOSUPPRESSIVE EFFECTS OF FR 900506 ON HUMAN T LYMPHOCYTE ALLOACTIVATION - Zeevi, A. (1987)
FR 900506 (FR) is a new immunosuppressive drug which prolongs allograft survival. Our studies have compared the in vitro inhibitory effects of FR and Cyclosporine (CsA) on human lymphocyte proliferation. Considerably lower doses of FR were required to induce inhibition of lymphocyte proliferation induced by concanavalin A (ConA) stimulation or in primary mixed lymphocyte reactions (MLR) Similar differences between FR and CsA were observed with the secondary stimulation of alloactivated T cells generated in MLR or propagated from liver transplant biopsies These observations provide further evidence that FR is about 500 fold more potent than CsA and may be a useful immunosuppressive agent in organ transplantation.